Novel mouse model of colitis characterized by hapten-protein visualization - Kazuhiro Ishiguro; Takafumi Ando; Osamu Maeda; Osamu Watanabe; Hidemi Goto (BioTechniques, 2010)
Trinitrobenzene sulfonic acid (TNBS) and oxazolone are used to induce colitis for the investigation of inflammatory reactions in the colon. Although these chemicals are presumed to bind proteins in the colonic mucosa and then induce colitis as haptens, hapten-protein formation has not yet been confirmed in the colonic mucosa. We developed a mouse model of colitis characterized by hapten-protein visualization, using 4-chloro-7-nitro-2,1,3-benzoxadiazole (NBD-Cl), which emits fluorescence after binding to proteins. The enema of 1 mg/mL NBD-Cl induced severe diarrhea, rectal bleeding, and body weight reductions in BALB/c mice. Mucosal signs indicative of colitis, such as redness and swelling observed under stereomicroscopy or inflammatory cell infiltration and crypt-epithelium destruction under microscopy, were manifested around NBD-proteins visualized with fluorescence. Fluorescence microscopy showed the infiltration of F4/80+ cells around areas of NBD-proteins, and flow cytometry indicated the uptake of NBD-proteins by CD11b+ cells. We also found critical roles for T cells and interleukin-6 in colitis induction with NBD-proteins. NBD-Cl-induced colitis presents a unique model to study the relevance between hapten-protein formation and inflammatory reactions and offers a method to assess experimental interventions on colitis induction in the mucosa, where hapten-protein formation is confirmed.